Election restrictions (Tanzania) - Voidly (2020)
CRITICAL severity censorship detected in Tanzania. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: TZ-2020-0001
Keywords: censorship; TZ; censorship; critical